Mapping Critical Residues in ATG11’s Coiled-Coil 2 Domain that Block Multiple Interactions and Disrupt Selective Autophagy - Meyer, Mitchell D.; Winzeler, Jasmine; Taylor, Sophia M.; Kilgore, Alex; Edicha, Kimberly; Chitwood, Chase; Spearin, Zachary; Silvia, S. K. Nadia Rahman; Chakraborty, Ronith; Smith, Jesse E.; Kennedy, Bridget; Zois, Carson; et al. (Frontiers in Cell and Developmental Biology, 2022)
Selective autophagy is a conserved subcellular process that maintains the health of eukaryotic cells by targeting damaged or toxic cytoplasmic components to the vacuole/lysosome for degradation. A key player in the initiation of selective autophagy in S. Cerevisiae (baker’s yeast) is a large adapter protein called Atg11. Atg11 has multiple predicted coiled-coil domains and intrinsically disordered regions, is known to dimerize, and binds and organizes other essential components of the autophagosome formation machinery, including Atg1 and Atg9. We performed systematic directed mutagenesis on the coiled-coil 2 domain of Atg11 in order to map which residues were required for its structure and function. Using yeast-2-hybrid and coimmunoprecipitation, we found only three residues to be critical: I562, Y565, and I569. Mutation of any of these, but especially Y565, could interfere with Atg11 dimerization and block its interaction with Atg1 and Atg9, thereby inactivating selective autophagy.